UJI ZPT HANTU DAN PUPUK NPK TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) DI MAIN NURSERY - Enny Mutryarny; Seprita Lidar (Universitas Lancang Kuning, 2016)
Oil palm (Elaeis guineensis Jacq) is one of Indonesia's mainstay plantation commodities and plays an important role for the national economy. Oil palm and plantations managed by state-owned enterprises, this is due to the increasing demand for palm oil in the industrial market. With the continuous development of oil palm plantations so that the provision of seeds should be considered because the success of planting in the field and the production of production is highly dependent on the quality of the seeds of oil palm plants used. Efforts that can be done to accelerate the growth of seeds Main Nursery is to provide NPK fertilizer and growth regulatory substances (ZPT) Hantu that can help the absorption of nutrients and accelerate the growth of vegetative plants. The aim of this research is to get the interaction of ZPT Hantu concentration and NPK fertilizer dosage which give the best influence to the growth of oil palm seed (Elaeis guineensis Jacq) in Main-nursery. The experiment was conducted experimentally with factorial Randomized Design (RAL), consisting of 2 factors ie H factor is ZPT Hantu and N factor is NPK fertilizer (16:16:16) which each consist of 3 levels. Thus obtained 9 treatment combinations with 3 replications. The observed data were analyzed by Duncan's multipoint test and Duncan's multiplexed test of 5%. Test of ZPT Hantu and NPK fertilizer significantly affect the growth of oil palm seedlings in Main Nursery that is on the parameters of seed height, stem diameter, leaf number and leaf area, whereas the combination of both only on bar diameter parameters that gives a real effect, with best treatment is combination giving ZPT Hantu 2 cc / l water and NPK 20 grams / plant.